Evaluating the correlation between Innovation in HR practices and organizational performance using Shapley Value - Jeidane, Mohammed El Mehdi (Université d'Ottawa | University of Ottawa, 2020)
Even though extensive research has been conducted on the potential that workers have on the productivity and profitability of a firm, not many scholars have based their findings and analysis with the use of the Shapley value tool. There is a possibility that Human Resource (HR) functions do have a positive impact on a firm's productivity, and the study aims at deducing both supporting and contrasting evidence concerning the same. The study below offers a detailed introduction of the status quo concerning Human Resource Management and offers a brief view of the papers and the objectives of the study. The literature review provides a detailed analysis of previous works building on the work of Huselid (1995) and others. The segment offers a preview of how other scholars felt and discovered the link between Human Resources practices and organizational performance. Most of the study is supportive of the idea that the Human Resources department and its practices correlate with the way a firm is performing, and it is mostly a positive one and that an improved Human Resources Management system would offer even better results. Little empirical data is availed by the review, which is why the paper details an investigation carried out in the field within the methodology and the data findings and analysis segment. The study collects data from about 160 participants, all working as employees or Human Resources officials in several companies within Canada. The findings are elaborated, and the discussions offer views based on the findings by the study. A conclusion offers a simplified summary of the research where Human Resources practices appear to correlate positively to organizational performance and, in some instances, negatively. The recommendations segment issues options of the steps the current Human Resources managers need to take to increase the efficiency of the department and the need for the installation of a strong and advanced innovatively and technologically Human Resources Management system. The study will also form a basis on which future researchers can base their studies.